Prevalence of acute respiratory infections in children under 5 years of age at a maternal-child health center in Lima - Córdova Sotomayor, Daniel Angel (2020)
Objective: To know the prevalence of acute respiratory infections in children under 5 years of age at a maternal-child health center in Lima. Materials and methods: This descriptive, observational, cross-sectional and retrospective study was conducted using 4,050 medical records from a maternal-child health center in Lima between January and September 2018. Inclusion criteria included legible and comprehensive medical records. Descriptive statistics was used. Results: The prevalence of acute respiratory infections was 30.47 %. Sex-adjusted prevalence was 31.8 % in males and 29.2 % in females. Age-adjusted prevalence was 29.5 % in children under 1 year old, 29.2 % in 2-year-old children, 35.3 % in 3-year-old children, 30.7 % in 4-year-old children and 28.0 % in 5-year-old children. The highest prevalence was found in April (59.4 %), followed by March (46.8 %), May (42.0 %) and August (the month with fewer cases). Conclusions: The prevalence of acute respiratory infections at a maternal-child health center in Lima was 30.47 %. The highest prevalence was observed in 3-year-old children and in April.